2000
DOI: 10.1034/j.1600-051x.2000.027012897.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent bacterial colonization of Porphyromonas gingivalis, Prevotella intermedia, and Actinobacillus actinomycetemcomitans in periodontitis and its association with alveolar bone loss after 6 months of therapy

Abstract: These data indicated that, in this population, the presence of P. gingivalis in plaque after treatment might be indicative of progressive alveolar bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 19 publications
6
84
1
5
Order By: Relevance
“…4). This result highlights the importance of the level of pathogen infection in alveolar bone resorption and is consistent with studies in humans that showed a correlation between the level of P. gingivalis infection in subgingival plaque and periodontal attachment loss (7,45,105). The final level of P. gingivalis infection in the LPS liposome-treated animals was ∼9-14% of the recoverable bacterial cell load, and this level still resulted in significant alveolar bone resorption (Fig.…”
Section: Figuresupporting
confidence: 77%
“…4). This result highlights the importance of the level of pathogen infection in alveolar bone resorption and is consistent with studies in humans that showed a correlation between the level of P. gingivalis infection in subgingival plaque and periodontal attachment loss (7,45,105). The final level of P. gingivalis infection in the LPS liposome-treated animals was ∼9-14% of the recoverable bacterial cell load, and this level still resulted in significant alveolar bone resorption (Fig.…”
Section: Figuresupporting
confidence: 77%
“…Antimicrobial chemotherapy may further suppress the periodontal pathogens and increase the benefits obtained by conventional mechanical treatment. Numerous systemic and local antimicrobial chemotherapeutic agents have been evaluated for the treatment of periodontitis with various degrees of success (5,19,37,41). A lack of effectiveness of some of the antibiotics used may be due to development of drug-resistant strains (10,29).…”
mentioning
confidence: 99%
“…It is an inflammatory process of periodontal tissues caused by bacterial infection which results in the destruction of periodontal connective tissue and resorption of alveolar bone. Porphyromonas gingivalis is believed to be one of the major pathogens in the etiology of adult periodontitis (5,37,38). Conventional mechanical debridement (i.e., scaling and root planing) can achieve a temporary decrease in the subgingival levels of P. gingivalis together with other pathogens (38).…”
mentioning
confidence: 99%
“…Antimicrobial chemotherapy may further suppress the periodontal pathogens and increase the benefits obtained by conventional mechanical treatment. Numerous systemic and local antimicrobial chemotherapeutic agents have been evaluated for the treatment of periodontitis with various degrees of success 5,6,7) . The effectiveness of these approaches are comprised by patient motivation, manual dexterity and the development of drug-resistant strains 8,9) .…”
Section: Original Articlesmentioning
confidence: 99%